Analisis Kepuasan Tenaga Kerja Outsourcing terhadap Pelayanan Perusahaan dengan Metode Importance-Performance Analysis (IPA) - Fuji Rahayu Wilujeng; Reynaldi Kusumo (JIEMS (Journal of Industrial Engineering and Management Systems), 2018)
Today, many companies outsource the new recruiting process. Recruitment of outsourced labor by the outsourcing service tenant is because the Company can reduce operating costs and improve the company. However, it is not comparable to outsourced employees to the services of tenant companies outsourcing services. Based on these conditions, the researchers analyze the relationship of employees in an outsourcing service company in Indonesia using Importance-Performance Analysis (IPA). The results show there are two attributes that belong to “concentrate these“category which means the company's performance has not been maximized for outsourcing employees. These attributes are the accuracy of salary payments and the nominal salary that is generated every month.